STRATEGI BELAJAR MEMBACA UNTUK ANAK TUNARUNGU - Azizah Arumsari (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2022)
The purpose of this study is to analyze strategies that make it easier to provide reading learning for deaf children.The research method used is a qualitative approach with the type of literature reviewresearch or library method. An online literature search was conducted through threeelectronic databases, namely from SAGE, Google Scholar and Proquest. The keywordsused in the search are strategy, reading, learning and deaf children. The researcherdetermined the criteria in the strategy of learning to read for deaf children to search for literature. The journal criteria determined by the researcher, followed by abstractselection, resulted in 41 articles: 14 from SAGE, Google Scholar 2 and 25 from Proquest. This resulted in 41 articles systematically reviewed: 14 articles from SAGE, Google Scholar 2 and 27 articles from Proquest, but those that met the criteria set by the researcher only got 2 articles that met the criteria.The results of the study found that the use of learning strategies used the reading methodby telling stories that were repeated using picture books and also using videos that weredisplayed and played repeatedly.